PENERAPAN ASAS UMUM PEMERINTAHAN YANG BAIK DALAM PENETAPAN CALON KEPALA DAERAH - Henry Soegeng (Fakultas Hukum Universitas Surabaya, 2018)
To create a corruption-free government could not be done just by establishing Indonesian Corruption Commission (KPK). As one of the most important principles in administrative law state, prevention is better than treatment, the attempt to create a corruption-free government should be done from the very beginning. Since the local government is elected by the people, the first step needed to be done is to make sure that only the corruption case-free people could compete to be the head of local government through an administrative decision of the electoral committee and electoral qualification. This paper is intended to critizise the conditions nowadays, where the corruption case suspects could make their way up to be the head of local government candidates.